Hubungan Antara Membaca Pemahaman dengan Kemampuan Menyelesaikan Soal Cerita Matematika Siswa Kelas IV - Sarlan Sarlan; Ida Bagus Kade Gunayasa; Abdul Kadir Jaelani (Program Studi Magister Pendidikan IPA, Universitas Mataram, 2022)
This research aims to find out the relationship between reading comprehension and the ability to solve mathematical story problems of students of grade IV SDN 32 Cakranegara. This research is a quantitative study with correlation analysis techniques. The population in this study is all students of IVA SDN 32 Cakranegara with a total of 33 students. The number of these populations is at once used as a sample of this study. The data collection technique in this study used test instruments that were previously piloted on 33 students to determine the validity and reliability. The analyst prasayarat test uses a normality test. Test the hypothesis used by Pearson Product Moment. The results showed there was a positive and significant relationship between reading comprehension with the ability to solve mathematical story problems in students of grade IV SDN 32 Cakranegara. This is shown from the results of the analysis of product correlation moments obtained a value of 0.065 with a significant value of 0.065 < 0.005 smaller than 0.05 at a significant level of 5%. This means that there is a significant relationship between reading comprehension and solving the problem of math stories class IV SDN 32 Cakranegara School Year 2020/2021.